Sexual Dysfunction in Post-Episiotomy and Post-Cesarean Mothers - Mairo, Queen Khoirun Nisa; Nugrahini, Evi Yunita (Humanistic Network for Science and Technology (Address: Cemara street 25, Ds/Kec Sukorejo, Ponorogo, East Java, Indonesia 63453), 2017)
Sexual Dysfunction in Post-Episiotomy and Post-Cesarean Mothers